2021
DOI: 10.1021/acs.jpcc.0c11519
|View full text |Cite
|
Sign up to set email alerts
|

H Resurface and Hot H Promoted H2 Recombination on Ni(111): Effects of Arrangement, Surface Coverage, and Lattice Motion

Abstract: Subsurface H can affect catalytic reactivity and selectivity. H resurface and H2 recombination with a subsurface H on Ni(111) were investigated by the quantum instanton method, and the arrangement, surface coverage, lattice motion, and hot H effects were explored. The arrangement effect of a surface H and a subsurface H varied the H resurfacing rate constant by 57 times at 300 K. From the clean Ni(111) to two H adsorbed Ni(111), the increase of surface coverage suppressed the H resurfacing rate constant by fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 78 publications
(128 reference statements)
0
7
0
Order By: Relevance
“…Concerning the stability of the subsurface H atoms, for the Ni(111) surface dosed at low temperature, it has been demonstrated that they resurface with several tenths of electronvolt excess energy, 7,9,11 recombine with surface atoms, and desorb between 180 and 215 K as H 2 . 10,42 These experimental results have motivated many theoretical stud- [7][8][9]11,15,17,40,41,43 which found that the heights of the diffusion barriers from subsurface to surface sites depend on lattice relaxation, surface and subsurface H coverages, and also, at low temperature, tunneling effects and correlated motion of the hydrogen and nickel atoms. Anyhow, there is a general agreement on the fact that a high occupation number of surface sites decreases the resurfacing rate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the stability of the subsurface H atoms, for the Ni(111) surface dosed at low temperature, it has been demonstrated that they resurface with several tenths of electronvolt excess energy, 7,9,11 recombine with surface atoms, and desorb between 180 and 215 K as H 2 . 10,42 These experimental results have motivated many theoretical stud- [7][8][9]11,15,17,40,41,43 which found that the heights of the diffusion barriers from subsurface to surface sites depend on lattice relaxation, surface and subsurface H coverages, and also, at low temperature, tunneling effects and correlated motion of the hydrogen and nickel atoms. Anyhow, there is a general agreement on the fact that a high occupation number of surface sites decreases the resurfacing rate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…4 θ Ni values are in principle possible when dosing H atoms, and in this respect we find that for the Ni(111) surface where all fcc and hcp sites are hydrogenated (θ Ni = 2 ML Ni ), the adsorption energy per H atom is −2.29 eV. However, for the bare Ni(111) exposed to the H atom flux, experimental results 6,10,12 and DFT calculations 15,17,40,41 indicate that at high surface coverage H atoms tend to penetrate subsurface, where they are kinetically trapped at metastable octahedral and tetrahedral sites. Moreover, subsurface H atoms can also easily diffuse deeper in the bulk.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 It has successfully predicted the rate constants and kinetic isotope effects for gas phase 55–57 and gas-surface reactions. 58–60…”
Section: Introductionmentioning
confidence: 99%
“…15 Moreover, non-metallic atoms such as N, P, and S facilitate electron redistribution and optimize the electronic structure, enhancing the adsorption of atomic hydrogen and organic molecules on the surface. 16 Previous literature indicates that Ni is effective in water electrolysis, 17 Mo is effective in hydrogen atom adsorption, 18 and the introduction of sulfur can improve reaction activity by altering the d-band position of transition metal elements. 19 Considering these factors, NiMoS should offer energy savings for water splitting and improved conversion rates for ECH.…”
Section: Introductionmentioning
confidence: 99%